Intravenous Tranexamic Acid and Lower Limb Arthroplasty—A Randomised Controlled Feasibility Study. Issue 4 (July 2018) - Painter, T. W.; Daly, D. J.; Kluger, R.; Rutherford, A.; Ditoro, A.; Grant, C.; Howell, S.
Tranexamic acid (TA) is widely reported to reduce bleeding and the risk of blood transfusion in patients undergoing lower limb arthroplasty. No study in this setting has had adequate power to examine for the effect of TA on either uncommon, but clinically important, adverse events or patient-centric endpoints. A large randomised controlled trial (RCT) is required to address these questions. As a preliminary feasibility study, we conducted an investigator-initiated, prospective, randomised, double blind placebo-controlled trial in 140 patients, aged 45 years or older, undergoing elective primary or revision hip or knee joint replacement. Subjects were randomised to receive intravenous (IV) TA or a placebo. The primary endpoints were the proportion of patients receiving allogenic blood transfusion and the feasibility of extending our trial methodology to a large trial of TA in this population. Secondary endpoints included a range of adverse clinical and surgical events as well as several patient-centric questionnaires. Red blood cell transfusion occurred in 15% of all patients prior to discharge from hospital. Transfusion rates were significantly different between the TA and placebo groups (8.5% versus 21.7%, P=0.03). Three out of four feasibility endpoints were met, with recruitment being slower than expected. No significant differences were seen between groups in the secondary endpoints. Despite a lower rate of transfusion than that widely reported, IV TA reduced transfusion in patients undergoing lower limb arthroplasty. Our trial methodology would be feasible in the setting of a large multicentre study to investigate whether TA is safe and reduces bleeding in lower limb arthroplasty.